(untitled) (Patrimônio e Memória, 2026)
The region called West of La Pampa (Argentina) is inhabited by rural population living dispersed in domestic and productive settlements, popularly known as puestos. For the most part of 20th century their architectures were produced in a self-managed way, with earthen and framework construction systems. Since 1990s it has been observed that their technological choices have been transformed risingly towards industrilised materials and techniques external to the region. Nevertheless, the local knowledge is still present in the domestic architectures and are recognised as immaterial heritage of La Pampa. The objective of this article is to inquire in the earthen and framework construction technologies more widely used in the region and the value that local population holds about them. In particular, fifty rural settlements were studied, which were located over the Atuel River basin in La Pampa. To this aim, a flexible qualitative methodology was chosen, combining different techniques: analysis of written and audiovisual records, literature review, interviews with inhabitants of the area, participant observation, visits, and graphic and photographic self-made registers. The results show the presence of regional variants of wattle and daub techniques, among which the chorizo technique stands out. Likewise, it is evident that the reduction in the use of regional systems takes place within a framework of contradictions and nostalgia.